The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2472555218813332
|View full text |Cite
|
Sign up to set email alerts
|

Positioning High-Throughput CETSA in Early Drug Discovery through Screening against B-Raf and PARP1

Abstract: Methods to measure cellular target engagement are increasingly being used in early drug discovery. The Cellular Thermal Shift Assay (CETSA) is one such method. CETSA can investigate target engagement by measuring changes in protein thermal stability upon compound binding within the intracellular environment. It can be performed in high-throughput, microplate-based formats to enable broader application to early drug discovery campaigns, though high-throughput forms of CETSA have only been reported for a limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The present study aimed to establish such a strategy, using the small molecule melatonin to improve AdMSC cell therapy. Such small cell-permeable molecules can provide robust and reproducible results, and affect signaling pathways (22). Additionally, the present study investigated whether melatonin treatment could improve the proliferative activity and anti-inflammatory effects of MSCs, and whether it could regulate the tri-lineage differentiation potential of MSCs compared with normal culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to establish such a strategy, using the small molecule melatonin to improve AdMSC cell therapy. Such small cell-permeable molecules can provide robust and reproducible results, and affect signaling pathways (22). Additionally, the present study investigated whether melatonin treatment could improve the proliferative activity and anti-inflammatory effects of MSCs, and whether it could regulate the tri-lineage differentiation potential of MSCs compared with normal culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…AlphaScreen CETSA has been reported in several studies. Shaw et al 15 examined B-Raf target engagement using HT-CETSA and identified 13 compounds from a set of 896 kinase inhibitors that thermally stabilized the protein. All 13 compounds had prior evidence of B-Raf binding and were tested at multiple concentrations to rank-order the inhibitor potencies.…”
Section: Ht-cetsa: Endogenous Proteinmentioning
confidence: 99%
“…Parallel developments in this field have also afforded microplate-based high-throughput variants of CETSA to expand applications to screening, structure–activity relationship (SAR), and mechanism-of-action (MoA) profiling. 9,3035 Our significant interest in the SAR and MoA areas triggered a further annotation of the literature with regard to their experimental details, with an emphasis on aspects that affect apparent compound potency. This includes the transient heat pulse design, whether compound was washed away prior to heating (e.g., through trypsinization), the inclusion of more than one compound to understand whether observed data agree with other measures of SAR, and whether the compounds were tested at multiple concentrations.…”
Section: Literature Annotationmentioning
confidence: 99%